Revolutionizing Business Intelligence: An AI-Driven Approach to Automated Insights - Dattatreya Raychowdhuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of integrating Artificial Intelligence into Business Intelligence (BI) systems to redefine how organizations manage and consume insights. Traditional BI relies heavily on users navigating reports, dashboards, spreadsheets, and databases to extract actionable information, often leading to inefficiencies, delayed decision-making, and overlooked critical insights. The proposed AI-enhanced BI framework addresses these challenges by automating exception management, alert generation, root cause analysis, insight discovery, quality assurance, and user-specific notifications. The system leverages AI to monitor BI platforms continuously, identifying anomalies, generating alerts for critical events, and performing automated root cause analyses to provide immediate context for exceptions. By understanding user roles, preferences, and interests, the AI delivers personalized notifications tailored to the user’s specific domain. The article discusses implementation strategies, including natural language processing, machine learning, and predictive analytics, while addressing challenges like data privacy, scalability, and integration with existing BI tools. This AI-driven paradigm positions BI not just as an analytical tool but as an intelligent partner, ensuring organizations remain informed, agile, and competitive in an increasingly data-driven world.